The Development of Performance-Based Seismic Structural Design Concepts in Indonesia: A Literature Review - Faradhiya Jinan Bastini; Abd Basit Amir; Fitri; Andi Hasri Tri Ulandari; Ira Suartika (Teknik Sipil Universitas Cahaya Prima, 2026)
Indonesia is situated in a region of high seismic activity; therefore, earthquake-resistant structural design constitutes a critical component of the national construction system. The conventional force-based design approach, which remains predominant in national standards, has inherent limitations in controlling damage levels and post-earthquake structural performance. In contrast, the concept of Performance-Based Seismic Design (PBSD) has evolved internationally as an approach that explicitly defines structural performance objectives. Although numerous studies in Indonesia have examined nonlinear analysis and building performance evaluation, integrated literature reviews addressing the development of PBSD concepts within the national context remain limited. This study aims to synthesize the development of performance-based seismic structural design and to identify its implications for enhancing building resilience in Indonesia. A qualitative approach was employed using a narrative literature review method covering national and international publications from 2000 to 2025, as well as relevant technical standard documents. The analysis was conducted through thematic categorization to map the evolution of conceptual frameworks, nonlinear analytical methods, and their integration into national regulations. The findings indicate that PBSD has evolved from a force-based approach toward performance- and displacement-based frameworks, supported by nonlinear analytical methods such as pushover analysis and nonlinear time history analysis. However, its implementation in Indonesia remains partial and requires strengthened regulatory frameworks as well as enhanced professional capacity. Systematic integration of PBSD has significant potential to improve safety, reduce damage risk, and strengthen the seismic resilience of building structures in the future.